Crash-Induced Vibration and Safety Assessment of Breakaway-Type Post Structures Made of High Anticorrosion Steels - Sang-Youl Lee (Shock and Vibration)
This study deals with car crash effects and passenger safety assessment of post structures with breakaway types using high performance steel materials. To disperse the impact force when a car crashes into a post, the post could be designed with a breakaway feature. In this study, we used a new high anticorrosion steel for the development of advanced breakaways. Based on the improved Cowper-Symonds model, specific physical properties to the high anticorrosion steel were determined. In particular, the complex mechanism of breakaways was studied using various parameters. The parametric studies are focused on the various effects of car crash on the structural performance and passenger safety of breakaway-type posts. The combined effects of using different steel materials on the dynamic behavers are also investigated.